Shopper: A System for Executing and Simulating Expressive Plans - Goldman, Robert; Maraist, John (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
We present Shopper, a plan execution engine that facilitates experimental evaluation of plans and makes it easier for planning researchers to incorporate replanning. Shopper interprets the LTML plan language, which extends PDDL in two major ways: with more expressive control structures, and with support for semantic web services modeled on OWL-S. LTML’s command structures include not only conventional ones such as branching, iteration, and procedure calls, but also features needed to handle HTN plans, such as precondition-filtered method choice. Unlike conventional programming languages, LTML supports interaction with the agent’s belief store, so that its execution semantics line up with those assumed by planners. LTML actions extend PDDL actions in having outputs as well as effects, which means that they can support actions that sense the world; an important special case of this is semantic web services, which reveal information about a state hidden from the agent. To support experimentation as well as action in the real world, Shopper accommodates multiple, swappable implementations of its primitive action API. For example, one may interact with real web services through SOAP and WSDL, or with simulated web services through local procedure calls. We describe novel features of LTML, the interpretation strategy, swappable back-ends, and the implementation.